PENGARUH GAYA KEPEMIMPINAN TRANSAKSIONAL DAN KOMPENSASI TERHADAP KOMITMEN PT AMERTA GIRI LESTARI YOGYAKARTA - Putut Wibowo (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to determine the effect of transactional leadership on commitment to PT Amarta Giri Lestari. To know influence of perception of compensation influence to commitment and effect of transactional leadership and perception of compensation simultaneously affect the commitment. The variables of this research are transactional leadership style, compensation and commitment. The population in this research is employees of PT Amarta Giri Lestari Yogyakarta, amounting to 50 people and also as a sample. Since all of the population were used as samples, this study used the census method. Method of taking data using questioner. The analysis technique used is multiple linear regression with 5% significance level. The result of the research is regression equation Y = 0,413X1 + 0,442X2. Transactional leadership has a positive and significant influence on the commitment of PT Amarta Giri Lestari Yogyakarta, this is indicated by the probability value (0.001) is smaller than the significant level of 0.05. The perception of compensation has a positive and significant impact on the commitment of PT Amarta Giri Lestari Yogyakarta, this is indicated by the probability value (0,000) smaller than the significant level of 0.05. Transactional leadership, and perception of compensation affect simultaneously to the commitment of PT Amarta Giri Lestari Yogyakarta, this is indicated by a significant level of 0.000 <0.05 (p <0.05). Commitment influenced Transactional leadership and perception of compensation by 53.1%. While the rest equal to 46.9% influenced by other factors.